Análisis de la transformación digital y cambio organizacional en empresas de servicios del Ecuador - Zambrano Boero, Omar Nicolas (2025)
Introduction The article examines digital transformation and its impact on organizational change within service companies in Ecuador. Objective Analyze how digital transformation influences organizational change in service companies in Ecuador, highlighting the effects of digitalization on operational efficiency, organizational culture and business strategies. Materials and Methods The study is based on an exhaustive literature review and documentary analysis, publishing relevant research and publications in the field of digital transformation and organizational change. It uses both physical sources (books and academic journals) and virtual sources (databases and digital libraries). Results 65% of service companies in Ecuador have initiated digital transformations in the last five years, which has resulted in a 20% increase in operational efficiency and a 15% reduction in costs. The findings underscore the importance of organizational citizenship behaviors, such as commitment and job satisfaction, for the success of organizational change. Conclusion Digital transformation emerges as a critical driver for organizational change in service companies in Ecuador. Companies that take a holistic approach to digitalization, considering both technological, human and strategic aspects, are better equipped to thrive in the changing business environment.